Validating the rhenium proxy for rock organic carbon oxidation using weathering profiles - Katherine E. Grant; Mathieu Dellinger; Alexander J. Dickson; Mateja Ogric; Kate Horan; Steven Petsch; Robert G. Hilton (Chemical Geology, 2025)

A Functional Response in Resource Selection Links Multiscale Responses of a Large Carnivore to Human Mortality Risk - Kyle D. Dougherty; Justin A. Dellinger; Bogdan Cristescu; Daniel J. Gammons; David K. Garcelon; J. Mark Higley; Quinton E. Martins; Seth P. D. Riley; Jeff A. Sikich; Thomas R. Stephenson; T. Winston Vickers; Greta M. Wengert; et al. (Ecology Letters, 2025)
Theory suggests that animals make hierarchical, multiscale resource selection decisions to address the hierarchy of factors limiting their fitness. Ecologists have developed tools to link population‐level resource selection across scales; yet, theoretical expectations about the relationship between coarse‐ and fine‐scale selection decisions at the individual level remain elusive despite their importance to fitness. With GPS‐telemetry data collected across California, USA, we evaluated resource selection of mountain lions ( Puma concolor ; n = 244) relative to spatial variation in human‐caused mortality risk. With hierarchical resource selection, coarse‐scale selection determines availability at finer scales. This simple relationship allowed us to demonstrate that functional responses in resource selection explicitly link individual‐level resource selection decisions across scales. We show that individuals proactively avoiding risk when selecting home ranges are freed to relax this avoidance when making decisions within home ranges. However, individuals also exhibit reactive avoidance of risk at the finest scales along movement paths.

Rhenium isotope variations in Icelandic groundwaters and hydrothermal systems - Wenhao Wang; Alexander J. Dickson; Mathieu Dellinger; Kevin W. Burton; Deirdre E. Clark; Guðjón Helgi Eggertsson; Íris Eva Einarsdóttir; Heimir Ingimarsson; Kiflom Gebrehiwot Mesfin; Robert G. Hilton; Julie Prytulak (Earth and Planetary Science Letters, 2024)

The use of long-read PCR amplicon sequencing to study the evolution of resistance to zoxamide, oxathiapiprolin and complex III inhibitors in French Plasmopara viticola field populations - S. Cherrad; B. Gillet; J. Dellinger; L. Bellaton; P. Roux; C. Hernandez; H. Steva; L. Perrier; S. Vacher; S. Hughes (Journal of Plant Diseases and Protection, 2024)

MelastomaTRAITs 1.0: A database of functional traits in M elastomataceae, a large pantropical angiosperm family - Marcelo Reginato; Carlos A. Ordónez‐Parra; João Vitor S. Messeder; Vinicius L. G. Brito; Agnes Dellinger; Ricardo Kriebel; Camilla Marra; Lilian Melo; Tatiana Cornelissen; Lisieux Fuzessy; Patricia Sperotto; Manuela Calderón‐Hernández; et al. (Ecology, 2024)
The recent availability of open‐access repositories of functional traits has revolutionized trait‐based approaches in ecology and evolution. Nevertheless, the underrepresentation of tropical regions and lineages remains a pervasive bias in plant functional trait databases, which constrains large‐scale assessments of plant ecology, evolution, and biogeography. Here, we present MelastomaTRAITs 1.0, a comprehensive and updatable database of functional traits for the pantropical Melastomataceae, the ninth‐largest angiosperm family with 177 genera and more than 5800 species. Melastomataceae encompass species with a wide diversity of growth forms (herbs, shrubs, trees, epiphytes, and woody climbers), habitats (including tropical forests, savannas, grasslands, and wetlands from sea level to montane areas above the treeline), ecological strategies (from pioneer, edge‐adapted and invasive species to shade‐tolerant understory species), geographic distribution (from microendemic to continental‐wide distribution), reproductive, pollination, and seed dispersal systems. MelastomaTRAITs builds on 581 references, such as taxonomic monographs, ecological research, and unpublished data, and includes four whole‐plant traits, six leaf traits, 11 flower traits, 18 fruit traits, and 27 seed traits for 2520 species distributed in 144 genera across all 21 tribes. Most data come from the Neotropics where the family is most species‐rich. Miconieae (the largest tribe) contains the highest number of trait records (49.6%) and species (41.1%) records. The trait types with the most information in the database were whole‐plant traits, flowers, and leaf traits. With the breadth of functional traits recorded, our database helps to fill a gap in information for tropical plants and will significantly improve our capacity for large‐scale trait‐based syntheses across levels of organization, plant–animal interactions, regeneration ecology, and thereby support conservation and restoration programs. There are no copyright restrictions on the dataset; please cite this data paper when reusing the data.

A thirty-year contaminant trend analysis in great lakes Native American fish harvests 1991–2021 - Matthew J. Dellinger; Lora Daskalska; Michael Ripley (Environmental Pollution, 2023)

Evaluation of Indoor and Outdoor Aquaculture Systems as Alternatives to Harvesting Hemolymph From Random Wild Capture of Horseshoe Crabs - Rachel Tinker-Kulberg; Anthony L. Dellinger; Lisa C. Gentit; Bryan A. Fluech; Cole A. Wilder; Ivy L. Spratling; David J. Stasek; Christopher L. Kepley; Lee Robertson; Melinda K. Goddard; Terry E. Brady; Lance Tōland; et al. (Frontiers in Marine Science, 2020)

Habitat use of sympatric prey suggests divergent anti-predator responses to recolonizing gray wolves - Justin A. Dellinger; Carolyn R. Shores; Apryle Craig; Michael R. Heithaus; William J. Ripple; Aaron J. Wirsing (Oecologia, 2019)

The ecological effects of providing resource subsidies to predators - Thomas M. Newsome; Justin A. Dellinger; Chris R. Pavey; William J. Ripple; Carolyn R. Shores; Aaron J. Wirsing; Christopher R. Dickman (Global Ecology and Biogeography, 2015)
Aim Predators often have important roles in structuring ecosystems via their effects on each other and on prey populations. However, these effects may be altered in the presence of anthropogenic food resources, fuelling debate about whether the availability of such resources could alter the ecological role of predators. Here, we review the extent to which human‐provided foods are utilised by terrestrial mammalian predators (> 1 kg) across the globe. We also assess whether these resources have a direct impact on the ecology and behaviour of predators and an indirect impact on other co‐occurring species. Location Global. Methods Data were derived from searches of the published literature. To summarise the data we grouped studies based on the direct and indirect effects of resource subsidies on predators and co‐occurring species. We then compared the types of predators accessing these resources by grouping species taxonomically and into the following categories: (1) domesticated species, (2) mesopredators and (3) top predators. Results Human‐provided foods were reported to be utilised by 36 terrestrial predator species in 34 different countries. In the presence of these resources we found that: (1) predator abundance increased, (2) the dietary preferences of predators altered to include the food subsidy, (3) life‐history parameters such as survival, reproduction and sociality shifted to the benefit or detriment of the predator, and (4) predators changed their home ranges, activity and movements. In some instances, these modifications indirectly affected co‐occurring species via increased predation or competition. Main conclusions The availability of human‐provided food to predators often results in behavioural or population‐induced changes to predators and trophic cascades. We conclude that there is an urgent need to reduce the access of predators to food subsidies to minimise human–wildlife conflicts and to preserve the integrity of ecosystem functioning in human‐influenced landscapes world‐wide.

Minimal Endocrine Alterations in Rodents After Consumption of Lake Trout ( Salvelinus namaycush ) - S. L. Gerstenberger; I. Heimler; R. Smies; R. J. Hutz; A. K. Dasmahapatra; V. Tripoli; J. A. Dellinger (Archives of Environmental Contamination and Toxicology, 2000)